Blocking TNF in vitro with infliximab determines the inhibition of expansion and interferon gamma production of Vγ9/Vδ2 T lymphocytes from patients with active rheumatoid arthritis. A role in the susceptibility to tuberculosis? - A. Principato; A. Ferrante; F. Ciccia; A. Accardo-Palumbo; A.R. Giardina; R. Impastato; G. Triolo (PAGEPress Publications, 2011)
Biological therapeutic agents neutralising tumour necrosis factor (TNF) are highly active in treating chronic inflammatory diseases, such as Crohn's disease, rheumatoid arthritis, ankylosing spondylitis, uveitis, and psoriasis (1-3). From the beginning, side effects of TNF neutralisation - mostly infectious complications - were recognized, the most important being, however, pulmonary tuberculosis infections (4).